The mushroom at the end of the world : on the possibility of life in capitalist ruins - Tsing, Anna Lowenhaupt (Princeton University Press, 2015)
A tale of diversity within our damaged landscapes, The Mushroom at the End of the World follows one of the strangest commodity chains of our times to explore the unexpected corners of capitalism. Here, we witness the varied and peculiar worlds of matsutake commerce: the worlds of Japanese gourmets, capitalist traders, Hmong jungle fighters, industrial forests, Yi Chinese goat herders, Finnish nature guides, and more. These companions also lead us into fungal ecologies and forest histories to better understand the promise of cohabitation in a time of massive human destruction